Method of in vitro isolation, proliferation and differenttiation of mesenchymal stem cells into osteoblasts in healthy and pathologic conditions - Ibrahim, Rashid; Kamran, Kareh; Abu Bakar @ Zakaria, Md Zuki; Tengku Ibrahim, Tengku Azmi (2010)
The present invention provides a method of in vitro cultivation of mesenchymal stem cells into osteoblasts, in which total bone marrow taken from a mammal is cultivated in a complete medium containing an increased amount of fetal bovine serum under standard conditions, subsequently the non-adherent cells are removed and the adherent cells are further expanded in a complete medium containing an increased amount of fetal bovine serum and after the expansion they are cultivated in an osteogenic inducing medium containing an increased amount of fetal bovine serum under standard conditions. The method is suitable also for bone marrow taken from a health-compromised mammal.